Theoretical Analysis and Experimental Research on Finishing Cut of Aviation Spiral Bevel Gears - Shufeng Yang; Hongtao Huang; Taolue Wen; Feng Wang; Yingjie Xu; Penghui Guo (Jixie chuandong)
Rolling finishing cut is a new kind of micro machining technology. It can remove the traces on the material surface， reduce the roughness of the tooth surface and reduce the meshing noise of the gear. An experimental study on finishing cut of aviation spiral bevel gears is carried out using parallel spindle rolling finishing technology. The machining mechanism of this finishing technology is described， and the relative movement between finishing abrasive and gear surface is studied. According to the cutting formula of abrasive at the outer circle of gears， the influence law of various factors is analyzed. The experimental results show that: the surface finishing of spiral bevel gears can be significantly improved by this kind of rolling finishing technology； the roughness Ra value of cone shaft tooth surface decreases from 0.8 to 0.4； the roughness Ra value of cone disk decreases from 0.8 to 0.3； the consistency of tooth surface texture is obviously improved. These lay a foundation for further research on vibration and noise characteristics of spiral bevel gears.